2021
DOI: 10.1109/access.2021.3074710
|View full text |Cite
|
Sign up to set email alerts
|

The Collaborative Power Inspection Task Allocation Method of “Unmanned Aerial Vehicle and Operating Vehicle”

Abstract: In order to overcome the short battery life and poor long-distance maneuverability of Unmanned Aerial Vehicle (UAV) in power inspection operations, some provincial and municipal power companies promote a new mode of "UAV and operating vehicle (OV)" collaborative power inspection. This paper investigates into the actual problems in the cooperative inspection operations of the OV and multi-UAVs, and proposes a model of task allocation for the cooperative inspections of the OV and multi-UAVs, which includes four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For the robot used in this study, we chose an LBR Iiwa robot arm, that was securely affixed to a table for its task. An inspection task was selected for the study, representative of tasks commonly found in industrial production [55,56]. More specifically, the selected task required the robot to inspect specific documents (see Fig.…”
Section: Experimental Taskmentioning
confidence: 99%
“…For the robot used in this study, we chose an LBR Iiwa robot arm, that was securely affixed to a table for its task. An inspection task was selected for the study, representative of tasks commonly found in industrial production [55,56]. More specifically, the selected task required the robot to inspect specific documents (see Fig.…”
Section: Experimental Taskmentioning
confidence: 99%
“…It has the advantages of simplicity, wide applicability, and fast convergence speed. Therefore, it is frequently applied to solve multi-UAV task assignment problems [34][35][36]. The basic process of the k-means clustering algorithm is commonly represented as:…”
Section: Coverage Scanning Clustering Algorithm-based Coverage-path P...mentioning
confidence: 99%